The Mediating effect of brand image on the relationship between internal incentives, sales promotion, and sales performance: a case study of WOM Finance - Agung Triwibowo; Bernard Tirtomoeljono Widjaja (Jurnal Mantik, 2026)
In the competitive financing sector, inconsistencies between marketing efforts and actual sales highlight a critical gap regarding brand perception. This study investigates the direct and indirect effects of internal incentives and sales promotion on sales performance, evaluating brand image as a mediator. A quantitative approach was employed, surveying 127 respondents (Marketing Agent Officers (MAOs), Branch Agency Heads (BAHs), dan Credit Marketing Officers (CMOs), dan Branch Marketing Heads (BMHs)) at WOM Finance. Data from Likert-scale questionnaires were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The sampling technique employed in this study is accidental sampling (convenience sampling). The choice of convenience sampling was based on considerations of ease and speed. This method is frequently selected when the population is relatively accessible, yet drawing a truly random sample is not feasible. The results demonstrated that internal incentives (?=0.272, p=0.017) and external promotion (?=0.211, p=0.008) significantly improved sales performance. Furthermore, brand image directly enhanced sales (?=0.366, p=0.029) and significantly mediated the impacts of both internal incentives (p=0.033) and promotion (p=0.037) on sales performance. These findings suggest that integrating internal employee motivation with external promotional efforts optimizes sales performance primarily by strengthening the corporate brand image, providing a holistic and robust framework for strategic marketing integration in the financial services industry.